Dumbo - Sharpsteen, Ben; Aberson, Helen (Buena Vista Home Entertainment ; distributed in the Philippines by Viva Video, 2002)
A baby elephant with oversized ears is ridiculed by all the circus animals and finally befriended by a mouse. Dumbo becomes the world's only flying elephant.